ENHANCING READING COMPREHENSION BY COMBINING PACA AND VIP STRATEGY AT THE SECOND GRADE SENIOR HIGH SCHOOL - Muhammad Dahlan,Firtriani ,Kamban (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2019)
The research aims at finding out whether or not the PACA and VIP strategies can enhance reading comprehension at the second-grade students of SMA Negeri 1 Nosu. This research used pre-experimental method. The second-grade students of SMA Negeri 1 Nosu in 2018/2019 academic year were the research pupaltions. The sample was 20 students. It used purposive sampling in one class. It is found that there is a significant difference between pre-test and post-test of the students’ achievement in reading comprehension. Therefore, it can be concluded that the use of combination PACA and VIP strategies in English language teaching can enhance the students’ reading comprehension.